Returning to the mission? Journalists after jail. Issue 6 (3rd July 2019) - Freedman, Eric
ABSTRACT: A growing number of journalists across the world are in prison for practicing their profession in ways that antagonise regimes, militaries, oligarchs, and other powerful interests. There have been studies by academics and press rights defenders of why journalists get imprisoned. In addition, human rights and press rights NGOs have investigated prison conditions for journalists. However, there is little published research about what journalists do after release. Do they resume their professional work, either in their home countries or in exile? How do prison experiences reshape their approach to journalism and relationships with news sources and colleagues? Based on in-depth interviews with eight formerly jailed journalists, with psychologists working with formerly jailed journalists, and with the executive director of a centre dealing with journalists' trauma, this exploratory study identified several common but not universal themes, including their views on the journalistic mission and the psychological ramifications of incarceration. It examines whether, how, and why they returned to the profession, additional constraints they may work under, and problems with post-traumatic stress disorder and other psychological conditions.